Landslide Treatment in the Al-Husainiyyah Junior High School Area using Cantilever-Geofoam Wall: Penanganan Longsor di Lingkungan SMP Al-Husainiyyah dengan Menggunakan Dinding Kantilever-Geofoam - Lim, Aswin; Pratama, Ignatius Tommy; Widjaja, Budijanto; Tjahjanto, Helmy Hermawan; Tjondro, Johannes Adhijoso; Wijaya, Obaja Triputera; Ginting, Bobby Minola; Setiawan, Theresita Herni; Adianto, Yohanes Lim Dwi; Hidayat, Felix; Hartieni, Patricia; William, Octavianus; Aldrianita, Tabitha; Fadhil, Imam Ahmad (Universitas Lancang Kuning, 2024)
A landslide triggered by heavy rainfall occurred in the Al-Husainiyyah Junior High School area on April 26th, 2023. The landslide damaged the nearby access roads, the existing retaining wall, and a futsal court threatening the safety of the teachers and students in conducting the learning activities that especially require open areas. Thus, this community service aims to provide a cantilever wall design with geofoam as an innovative lightweight backfill material to reinforce the slope and repair the damaged structures. Field surveying and numerical analysis were then conducted to understand the current slope and soil conditions and to analyze the stability of the slope and retaining wall. The results show that a cantilever wall with a total height of 1.8 m supported by a strauss pile row with a diameter of 0.4 m, 4 m in length, and 2.5 m in spacing could increase the stability of the slope.